Are employees with higher organization-based self-esteem less likely to quit? A moderated mediation model - Lin, Naiqing; Jang, Jichul; Roberts, Kevin R. (My University, 2018)
This study focuses on striving for achievement as an important antecedent forming Organization-Based Self-Esteem (OBSE) and the relationship between achievement striving and turnover intention in the hospitality industry. More specifically, employees with higher achievement striving traits show a stronger negative correlation between OBSE and turnover intention, through organizational commitment. An online survey was distributed to restaurant employees; 160 valid responses were analyzed. An analytic framework based on confirmatory factor analysis and logic regression was used to examine the hypotheses. The results show that organizational commitment fully mediated the relationship between OBSE and turnover intention, and higher levels of individual achievement striving significantly modified the conditional indirect relationship. The results showed that the mediation model and achievement striving strength accounted for 15.7% of the variance in turnover intention at the 50?th, 75?th, and 90?th level and was most effective for low OBSE employees. Theoretical implications and future research are included.
Citation: Lin, N., Jang, J., & Roberts, K. R. (2018). Are employees with higher organization-based self-esteem less likely to quit? A moderated mediation model. International Journal of Hospitality Management, 73, 116–124. https://doi.org/10.1016/j.ijhm.2018.01.021
Keywords: Organization-based self-esteem; Turnover intention; Achievement striving; Trait activation